2014
DOI: 10.1002/masy.201300152
|View full text |Cite
|
Sign up to set email alerts
|

Series of Poly(4‐vinylpyridine) Containing Quaternary Alkyl bromides: Synthesis and Determination Percentage of Quaternization

Abstract: Summary: In this study, we focus on the synthesis series of poly(4-vinylpyridine) (P4VP) containing quaternary alkyl bromides. The poly(4-vinylpyridine) (P4VP) was synthesized by conventional radical copolymerization and then the P4VP was quaternized by alkyl bromides containing chains consisting of 5 and 10 carbon atoms. Two copolymers series with three degrees of polymerization have been synthesized, the first poly[N-isopentyl(4-vinylpyridinium)] bromide P4VPIPBr (I); (II); (III) and the second poly[N-decyl(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In this respect, we note that vinylpyridinium monomers can undergo free radical polymerization, but the kinetic behavior is peculiar with a high reaction order in the monomer (e.g., 2.7), and thus, the polymerization is too slow in dilute solutions. Poly­(vinylpyridinium) polymers have also been obtained by free radical polymerization of vinylpyridine, followed by quaternization. , The RAFT polymerization of a vinylpyridium salt has apparently never been reported, although it has been shown that a controlled RAFT polymerization takes place for other cationic monomers, for instance, a styrene containing a benzylic pyridium substituent in the para position, CH 2 CH–C 6 H 4 -4-CH 2 C 5 H 5 N + Cl – . Additional control experiments have shown the absence of reactivity between the RAFT agent and the monomer, as well as between the RAFT agent and MeI.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, we note that vinylpyridinium monomers can undergo free radical polymerization, but the kinetic behavior is peculiar with a high reaction order in the monomer (e.g., 2.7), and thus, the polymerization is too slow in dilute solutions. Poly­(vinylpyridinium) polymers have also been obtained by free radical polymerization of vinylpyridine, followed by quaternization. , The RAFT polymerization of a vinylpyridium salt has apparently never been reported, although it has been shown that a controlled RAFT polymerization takes place for other cationic monomers, for instance, a styrene containing a benzylic pyridium substituent in the para position, CH 2 CH–C 6 H 4 -4-CH 2 C 5 H 5 N + Cl – . Additional control experiments have shown the absence of reactivity between the RAFT agent and the monomer, as well as between the RAFT agent and MeI.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its intrinsic pH responsivity, P4VP is suitable for post-polymerization modifications through the quaternization of the nitrogen atom via multiple types of halogenated molecules [ 32 , 33 , 34 , 35 ]. The possibility of using a broad range of compounds as a quaternization agent opens many opportunities for tuning the system as desired.…”
Section: Introductionmentioning
confidence: 99%